Recovery of Cobalt and Lithium from Spent Lithium Ion Batteries - N.E. Abdul Latif; A.M. Ahmed (Engineering and Technology Journal, 2017)
In this research a combination of mechanical separation, reductive leaching and chemical precipitation are used to regain Li as Li2CO3 and Co as Co(OH)2 from waste lithium ion batteries. First batteries are dismantled and different component are separated. Anode and cathode foils are grinded and sieved to extract Al and Cu from spent battery powder. The separation efficiency for copper and aluminum are 97.68% and 84.41% respectively. The separated powder is leached with sulfuric acid and hydrogen peroxide solution to dissolve cobalt and lithium. The effects of sulfuric acid concentration, time, temperature, concentration of hydrogen peroxide and S/L on the leaching efficiency for cobalt and lithium are studied. Design of experiments by Taguchi method is used to determine experiments conditions, analysis the results, and identify the optimum leaching conditions. The optimum leaching conditions are 1.5 M acid concentration, 60 minute, 60 °C, 15% H2O2, and 40 g/l solid to liquid ratio. Leaching efficiencies of 94.07% Co and 98.15% Li are achieved with these optimum conditions. Leaching solution of the optimum experiment is used to recover cobalt as cobalt hydroxide and lithium as lithium carbonate by chemical precipitation. An equivalent volume of 4M NaOH is used to precipitate cobalt as cobalt hydroxide. After 1 hour 99.98%, Co is precipitated and collected by filtration and dried. After collection of the Co(OH)2 product, the remaining solution is treated with equivalent volume of "saturated solution" of Na2CO3 at 100 °C to recover lithium as Li2CO3. After 1 hour, 80 – 85 % Li is precipitated, filtrated and dried. Precipitation products are investigated with XRD, which confirmed that cobalt hydroxide and lithium carbonate are recovered from leaching solution.